Explore Westonci.ca, the leading Q&A site where experts provide accurate and helpful answers to all your questions. Join our Q&A platform and connect with professionals ready to provide precise answers to your questions in various areas. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.

A, b, and c are polynomials, where a = n, b = 2n 6, and c = n2 – 1. what is ab – c in simplest form? –n2 3n 5 n2 6n 1 2n2 6n – 1 3n2 5

Sagot :

The equations a = n, b = 2n + 6 and c = n² - 1 are polynomials, and the expression for ab - c is n² + 6n + 1

How to determine the expression for ab - c?

The polynomials are given as:

a = n

b = 2n + 6

c = n² - 1

The expression ab - c is calculated using:

ab - c = n * (2n + 6) - (n² - 1)

Expand

ab - c = 2n² + 6n - n² + 1

Collect like terms

ab - c = 2n² - n² + 6n  + 1

Evaluate

ab - c = n² + 6n + 1

Hence, the expression for ab - c is n² + 6n + 1

Read more about polynomials at:

https://brainly.com/question/4142886

#SPJ4